Endoscopic ultrasound-guided through-the-needle microforceps biopsy improves diagnostic yield for pancreatic cystic lesions: a systematic review and meta-analysis - McCarty, Thomas; Rustagi, Tarun (Endoscopy International Open, 2020)
Background and study aims Given variable diagnostic yield of endoscopic ultrasound (EUS)-guided fine-needle aspiration (FNA) for pancreatic cystic lesions (PCLs), a through-the-needle (TTN) microforceps biopsy device passed through a 19-gauge FNA needle has been devised to improve tissue sampling. This was a systematic review and meta-analysis to evaluate the feasibility, diagnostic yield, and safety of EUS-guided TTN microforceps biopsy for diagnosis of PCLs.Methods Individualized searches were developed in accordance with PRISMA and MOOSE guidelines. This was a cumulative meta-analysis performed by calculating pooled proportions with rates estimated using random effects models. Measured outcomes included pooled technical success, diagnostic yield, accuracy, and procedure-associated adverse events (AEs) as well as comparison to conventional FNA.Results Eleven studies (n = 518 patients; mean age 64.13 ± 5.83 years; 58.19 % female) were included. Mean PCL size was 33.39 ± 3.72 mm with the pancreatic head/uncinate (35.50 %) being the most common location. A mean of 2.47 ± 0.92 forceps passes were performed with a mean of 2.79 ± 0.81 microbiopsies obtained per lesion. Pooled technical success was 97.12 % (95 % CI, 93.73–98.71; I2 = 34.49) with a diagnostic yield of 79.60 % (95 % CI, 72.62–85.16; I2 = 56.00), and accuracy of 82.76 % [(95 % CI, 77.80–86.80; I2 = 0.00). The pooled serious adverse event rate was 1.08 % (95 % CI, 0.43–2.69; I2 = 0.00). Compared to conventional FNA, TTN microforceps biopsy resulted in significant improvement in diagnostic yield [OR 4.79 (95 % CI: 1.52–15.06; P = 0.007)] and diagnostic accuracy [OR 8.69 (95 % CI, 1.12–67.12; P = 0.038)], respectively.Conclusions EUS-guided TTN microforceps biopsy appears to be safe and effective for diagnosis of PCLs with improvement in diagnostic yield and accuracy when compared to FNA alone.